Strict Liability and Negligence with Search for Precautionary Measures. (9th November 2021) - Baumann, Florian; Friehe, Tim
Abstract: This article explores the performance of strict liability and negligence when agents initially have imperfect information about what care options exist to influence expected accidental harm. A technology that establishes a basic level of care is commonly known in our framework, but whether a superior one exists is uncertain. Injurers and/or victims can engage in a costly search to find out. For this setup, we show that strict liability can induce lower social costs than negligence when the superior care technology's existence is moderately likely and agents' search costs are high, a combination likely to apply to new and complex activities. Instead, negligence is socially preferred when the superior care technology's existence is either very likely or very unlikely, or when search costs are low, configurations likely to apply to well-established activities.